A nanostructured bifunctional Pd/C gas-diffusion electrode for metal-air batteries. (20th August 2015) - McKerracher, R.D; Alegre, C.; Baglio, V.; Aricò, A.S.; Ponce de León, C.; Mornaghini, F.; Rodlert, M.; Walsh, F.C.
Graphical Abstract: Images showing (a) a scanning electrode microscope cross section of the Pd/C air electrode, (b) a TEM micrograph of the Pd/C catalyst, and (c) charge–discharge cycling of the air electrode in 6 mol dm −3 KOH at 20 mA cm −2 under 100 ml min −1 oxygen flow. Highlights: The Pd/C air electrode shows consistent good performance at modest current densities (20–80 mA cm −2 ), and is stable for 1000 cycles at room temperature. The Pd/C air electrode has a potential difference of 0.53 V between oxygen evolution and oxygen reduction. The air electrode makes efficient use of a small precious metal loading (0.5 mg cm −2 ), and is mainly made from lightweight carbon materials. The air electrode has better stability than a commercial 2 mg cm −2 Pt/C electrode on repeated charge–discharge cycling, despite having a lower (and therefore less expensive) loading of catalyst. Abstract: Designing a bifunctional air electrode which catalyses both the oxygen reduction and oxygen evolution reactions is an essential part of progress towards fully rechargeable metal-air batteries, such as the iron-air battery which is environmentally friendly, low cost, and does not suffer risk of thermal runaway like lithium-ion batteries. This paper reports the development of a lightweight carbon-based bifunctional air electrode, catalysed by a small (0.5 mg cm −2 ) loading of 30 wt.% palladium on carbon. The Pd-catalysed air electrode showed good bifunctional activity, with 0.53 V potential difference between oxygen reduction and evolution. The Pd/C air electrode showed improved catalytic activity at high current densities (≥ 50 mA cm −2 ) and enhanced durability compared with two commercial Pt/C air electrodes produced by Gaskatel GmbH and Johnson Matthey. A stable oxygen evolution potential was maintained over 1, 000 charge-discharge cycles.